The study on reliability of Ni-coated graphene doped SAC305 lead-free composite solders under high current-density stressing. Issue 4 (2nd September 2019) - Chen, Guang; Li, Jiqiang; Kuang, Xinwen; Wu, Yaofeng; Wu, Fengshun
Abstract : Purpose: The purpose of this paper is to investigate the effect of nickel-plated graphene (Ni-GNS) on the microstructure and mechanical properties of 96.5Sn3Ag0.5Cu (SAC305) lead-free solder joints before and after an electro-migration (EM) experiment. Design/methodology/approach: In this paper, SAC305 solder alloy doped with 0.1 Wt.% Ni-GNS was prepared via the powder metallurgy method. A U-shaped sample structure was also designed and prepared to conduct an EM experiment. The EM experiment was carried out with a current density of 1.5 × 104 A/cm2. The microstructural and mechanical evolutions of both solder joints under EM stressing were comparatively studied using SEM and nanoindentation. Findings: The experimental results showed that for the SAC305 solder, the interfacial intermetallic compounds (IMC) formulated a protrusion with an average height of 0.42 µm at the anode after 360 h of EM stressing; however, despite this, the surface of the composite solder joint was relatively smooth. During the stressing period, the interfacial IMC on the anode side of the plain SAC305 solder showed a continuous increasing trend, while the IMC at the cathode presented a decreasing trend for its thickness as the stressing time increased; after 360 h of stressing, some cracks and voids had formed on the cathode side. For the SAC305/ Ni-GNS composite solder, a continuous increase in the thickness of the interfacial IMC was found on both the anode and cathode side; the growth rate of the interfacial IMC at the anode was higher than that at the cathode. The nanoindentation results showed that the hardness of the SAC305 solder joint presented a gradient distribution after EM stressing, while the hardness data showed a relatively homogeneous distribution in the SAC305/ Ni-GNS solder joint. Originality/value: The experimental results showed that the Ni-GNS reinforcement could effectively mitigate the EM behavior in solder joints under high current stressing. Specifically, the Ni particles that plated the graphene sheets can work as a fixing agent to suppress the diffusion and migration of Sn and Cu atoms by forming Sn-Cu-Ni IMC. In addition, the nanoidentation results also indicated that the addition of the Ni-GNS reinforcement was very helpful in maintaining the mechanical stability of the solder joint. These findings have provided a theoretical and experimental basis for the practical application of this novel composite solder with high current densities.